Physical characterization of propolis encapsulated vitamin E TPGS as nanomedicine (Corrected Proof) - Tong Kong, Yee; Kutty, Rajaletchumy V. (Elsevier, 2021)
CAPE found in propolis has become the subject of research interest as it has various medicinal benefits such as antiviral, anti-inflammatory, antioxidant, anticancer and immunomodulatory properties [1]. In this study, propolis obtained in Kuantan, Pahang is encapsulated using biodegradable polymer, vitamin E TPGS as a drug delivery system whereas TPGS-CAPE is used as a control. The findings show the physical characterization of propolis loaded vitamin E TPGS polymeric micelles which includes size, polydispersity index, zeta potential, shape and morphology and encapsulation efficiency